EVALUATION OF XANTHINE OXIDASE INHIBITORY ACTIVITY BY FLAVONOIDS FROM PONGAMIA PINNATA LINN - Bambrana, Vanishree; Cd, Dayanand; Sr, Sheela (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: Flavonoids from the crude seeds extract of Pongamia pinnata L., dried fruit powder of Morinda citrifolia L., bark of Mangifera indica L., and rhizome of Zingiber officinale Rosc. were screened for xanthine oxidase (XO) inhibition at different concentration. The inhibitory potential of quercetin and allopurinol were used for the determination of 50% inhibitory concentration (IC50) and Ki values. Methods: Isolation of flavonoids from the plant extracts was processed by column chromatography and tested for XO inhibitory activity in the range of 6-800 Î¼g/ml. Results: The results demonstrated that optimized flavonoids extract of P. pinnata L. exhibited promising XO inhibition. P. pinnata L., M. indica L., and Z. officinale Rosc. had IC50 in the concentration of 8.74 mM, 1.09 mM, 5.4 mM and Ki 0.35 mM, 1.73 mM, 2.7 mM, respectively. Conclusion: The study showed that plant species under investigation exhibited XO inhibition by optimized flavonoid extract. P. pinnata L. indicated promising XO inhibition compared to other plant extracts. Flavonoids can be used as a potent inhibitor of XO an alternative to allopurinol. Keywords: Xanthine oxidase, Quercetin, Allopurinol, Pongamia pinnata, Oxidative stress.